Assembly of functional microbial communities in paddy soil with long-term application of pig manure under rice-rape cropping system. (1st March 2022) - Hou, Qiong; Lin, Sen; Ni, Yuemin; Yao, Longren; Huang, Shan; Zuo, Ting; Wang, Jian; Ni, Wuzhong
Abstract: Organic farming is considered an efficient approach to improve soil fertility for sustainable agriculture. However, its soil micro-ecological effects and functions in intensive rice cropping systems are still obscure. Twelve soil samples were collected from a field experiment with four treatments such as M0 (no pig manure), M1 (1.6 t ha −1 pig manure), M2 (3.2 t ha −1 pig manure) and M3 (4.8 t ha −1 pig manure) after eight rice-oilseed rape rotation. Soil chemical property, enzyme activity and abundant/rare bacterial or fungal communities were analyzed to investigate the effect of conversion to organic farming with continuous pig manure application on soil microbiota. Stochastic processes controlled the assembly of abundant taxa, and deterministic processes dominated rare taxa. The composition and network construction of bacterial and fungal communities were significantly affected by pig manure, with changes in soil property and enzyme activity. Based on partial least squares path modeling (PLS-PM), pig manure application affected bacteria construction and enzyme activities by increasing soil carbon (C) and nitrogen (N). In summary, long-term pig manure application promotes specific microbial associations known to be involved in degrading complex organic compounds, and improving soil fertility such as soil enzyme activities. This research provides insight into understanding the processes behind changes in bacterial and fungal communities in paddy soil after conversion to organic farming. Graphical abstract: Image 1 Highlights: Pig manure enhances soil fertility by improving soil properties and enzyme activities. Pig manure alters soil abundant/rare bacterial and fungal composition and assembly. Soil enzyme activities were closely linked with bacteria rather than fungi. Rare taxa are more important in co-occurrence network.